EFFECTIVENESS OF KINESIOLOGIC TAPE APPLICATION IN ROTATOR CUFF INJURIES - Reyhan, Aycan Çakmak (IJPHY PUBLISHERS, 2018)
Background: In our study, it was aimed to research the effect of kinesiological tape on pain, shoulder movement angles, and daily life activities. Methods: The control group (n:15) was applied with classical physiotherapy program including ultrasound, tens and exercise. The experiment group (n:15) was applied kinesiological-tape for seven days in addition to classical physiotherapy and rehabilitation program. Pretreatment and post-treatment pains of the patients were measured by using Visual Analog Scale (VAS), the goniometer was used to measure the shoulder ranges, Constant-Murley measured daily life activity levels, and DASH-T measured shoulder disability level. Results: As the VAS scores of the control group inactivity reduced by 11,21 points, the scores of the experiment group decreased by 24,53 points. The difference in scores between the two groups is significant statistically (p<0,05). As the extension and abduction scores increased significantly more in the experiment group, flexion increase is more at the control group. However, the difference between the two groups in shoulder movement angles was not found significant statistically (p>0,05). For shoulder movement opening, all records of the experiment group are significantly better than that of the control group, except the flexion increase. Conclusion: Kinesiological tape application ensuring a reduction in pain for rotator cuff injury in a shorter period is a treatment also providing significantly better results in shoulder movement recovery, increase in functionality, and a decrease in disability.
Keywords: Kinesiologic Tape; Physical Therapy; Constant Murley; Visual Analog Scale; Daily Life Activities; Rotator Cuff